Afghan peace talks historic opportunity to end 4 decades of war - Eishan Jan, Mohammad Naqib (Malaysiakini, 2020)
Today, the long-awaited intra-Afghan peace negotiation commences in Doha, Qatar. This vitally important direct negotiation between the Afghan government and the Taliban represent a step forward in ending the war and bringing a just and durable peace to Afghanistan.